Prevalence of Human Papillomavirus and Genotype Distribution in Chinese Men: A Systematic Review and Meta‐Analysis - Yifan Li; Fan Zhao; Dan Wu; Chuanyu Qin; Yajiao Lu; Ying Yang; Hairong Wang; Chunlei Lu; Shengyue Qiu; Wenwen Jiang; Yuxiu Yan; Xianyi Geng; et al. (Cancer Medicine)
ABSTRACT Background Human papillomavirus (HPV) vaccination represents a cost‐effective strategy for preventing HPV‐related diseases across genders. However, the HPV vaccine has not been approved for mainland Chinese males, and the comprehensive epidemiological landscape of HPV among Chinese males from mainland China is limited. Methods This study aimed to address this gap by examining HPV infection data in Chinese males from January 2012 to September 2024. Four English databases (Web of Science, Embase, Medline, and Cochrane Library) and four Chinese databases (CNKI, VIP, Wanfang, and SinoMed) were systematically reviewed. Random effect models assessed pooled HPV prevalence, and subgroup analyses were conducted based on population (outpatients vs. health checkups). Genotype‐specific HPV positivity was calculated. Results A total of 296 studies were included, encompassing 199,233 outpatients and 16,452 health checkups. HPV prevalence was 52.45% among outpatients, with the most prevalent subtypes being HPV 6 (19.06%), 11 (13.71%), and 16 (8.29%). Among health checkups, HPV prevalence was 7.89%, with the highest prevalence subtypes being HPV 16 (3.66%), 52 (1.37%), and 58 (1.19%). Among male patients diagnosed with cancer, HPV 16 (18.50%) and 18 (5.33%) were the most common subtypes, and HPV prevalence was 82.11% among the HIV‐positive MSM population. Conclusion The high prevalence of HPV among Chinese males, particularly among outpatients and the HIV‐positive MSM population, underscores the urgent need for targeted prevention strategies. The common subtypes identified in this analysis highlight the potential benefits of introducing HPV prophylactic vaccines to Chinese males, which could significantly reduce the burden of HPV‐related diseases across the population.